TREATMENT STRATEGY FOR INFECTIONS CAUSED BY HIGHLY DRUG-RESISTANT (XDR) STRAINS OF PSEUDOMAS AERUGINOSA IN CANCER PATIENT - Z. V. Grigoryevskaya; I. N. Petukhova; S. A. Dyakova; N. V. Dmitrieva (Сибирский онкологический журнал)
The problem of nosocomial infections caused by Pseudomonas aeruginosa is still being actively discussed in the medical published literature. Special attention is paid to the infectious complications caused by highly resistant (XDR – extremelyor extensively-drug-resistant) strains of P. aeruginosa which are associated with increased length of hospital stay and increased cost of treatment and mortality rates. Immunocompromised cancer patiens are at significant high risk for infections caused by XDR strains. The development of antibiotic regimens for the treatment of nosocomial infections caused by strains of XDR-P. aeruginosa is of great importance.